Mycorrhizal symbiosis and application of vitamin B3-treated Trichoderma Harzianum HE24 additively trigger immunity responses in faba bean plants against Rhizoctonia root rot and promote the plant growth and yield - Hany H.A. El-Sharkawy; Younes M. Rashad; Salama S. A. El-Blasy; Basma H. Amin; Mahmoud A.A. Youssef; Mohamed Hafez; Ahmed Abd-ElGawad; Mohamed Bourouah; Elsherbiny A. Elsherbiny; Safaa A. Yousef (BMC Plant Biology)
Abstract Background Faba bean is a valuable legume crop, known for its high nutritional value and nitrogen fixing ability. Rhizoctonia root rot of faba bean, caused by Rhizoctonia solani, severely affects the plant growth and yield. This study aimed to evaluate the effect of symbiosis with arbuscular mycorrhizal fungi (AMF) and application of vitamin B3-treated Trichoderma harzianum HE24 on plant immune responses against Rhizoctonia root rot under greenhouse conditions. Results Results revealed that symbiosis with AMF and the application of vitamin B3-treated T. harzianum HE24 significantly upregulated the defense-related genes CHI II (50.2-fold), PAL1 (13.3-fold), and HQT (37.0-fold). Additionally, this combined treatment led to an increment in the enzymatic activity of peroxidase and polyphenol oxidase recording 23.7 and 14.6-unit min−1g−1 fresh weight, respectivly. Furthermore, the phenolic content in faba bean plants was enhanced (1402.3 mg/g fresh weight) suggesting a strong activation of the plant’s biochemical defense mechanisms and metabolic activities. Rhizoctonia root rot severity in faba bean plants was reduced by 80.4% following this treatment. Moreover, the results demonstrated that AMF symbiosis notably improved plant growth, photosynthetic content, and yield, compared to the infected control, leading to enhanced overall plant performance and disease resistance. Conclusions These findings suggest that the additive interaction between AMF and vitamin B3-treated T. harzianum HE24 provides an effective, eco-friendly alternative for managing root rot of faba bean.